Analisis Kapasitas Pelayanan Publik Pemerintahan Desa Studi Kasus Di Desa Cibuntu Kecamatan Cibitung Kabupaten Bekasi Propinsi Jawa Barat - Bambang Istianto; Taufan Maulamin (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2019)
The purpose of the research is to do the analysis of public service capacity at the Village government through the case study in the Cibuntu Village, Cibitung district, Bekasi – Regency in the province of West- Java. The method of research used is the method of qualitative descriptive analysis. The collection of data is based on the field observationand grounded research as well as in-depth interview with a number of key infomants. The research result found is the public service capacity at the village government is still very weak. The low public service capacity is caused by ineffectiveness of village government organization, the low competency of human resouurces of Village apparaturs. The ineffectiveness of Village financial governance and the weakness of Village government leadership. Based on the research result, it is suggested that the Village government organization, the incrased competence of the Village apparaturs be more effective and the selection of Vilage chief election based on meritorious system.